The Role of Historical Resource Constraints in Modern Gender Inequality: A Cross-Country Analysis - Gautam Hazarika; Chandan Kumar Jha; Sudipta Sarangi (Institute for the Study of Labor (IZA), 2014)
We posit that historical resource scarcities played a role in the emergence of gender norms inimical to women that persist to this day. This thesis is supported by our finding that nations historical resource endowments, as measured by the historical availability of arable land, are statistically significantly negatively related to their present levels of gender inequality, as gauged by the United Nations Development Programmes Gender Inequality Index.
Keywords: N90; O15; 330; scarcity; culture; history; gender